Two new species of the genus Noonamyia from Hainan in China (Diptera, Lauxaniidae) - Shi, Li; Yang, Ding (Zootaxa, 2009)
The genus Noonamyia Stuckenberg, 1971 is recorded from China for the first time. The following two species are described as new to science: Noonamyia bisubulata sp. nov. and Noonamyia umbrellata sp. nov. A key to separate these species is presented.